Preoperative Mannitolization Can Decrease Corneal Endothelial Cell Damage After Cataract Surgery. (1st September 2016) - Hwang, Ho Sik; Ahn, Yong Sun; Cho, Yang Kyung
ABSTRACT: Purpose : To evaluate whether preoperative mannitolization can change ocular biometry and affect postoperative corneal endothelial cell density. Methods : Bilateral sequential cataract surgery was performed in 38 patients. Preoperative mannitolization was done in one eye of each subject. We checked the change in preoperative ocular biometry before and after intravenous mannitolization. We compared the postoperative corneal endothelial cell density between eyes with mannitolization and without mannitolization at postoperative week 1, 2, 5, and 8. We evaluated the relationship between change in ocular biometry and change in postoperative corneal endothelial cells in eyes that underwent preoperative mannitolization. Results : After mannitolization, eyes exhibited decreased intraocular pressure, axial length (AL), and vitreous chamber depth (VCD) and increased anterior chamber depth (ACD) and lens position (LP) compared to before mannitolization ( p < 0.05). Preoperative mannitolization has a tendency to decrease the intraoperative use of phaco energy in eyes with moderate nucleosclerosis. Eyes with preoperative mannitolization showed less loss of postoperative corneal endothelial cells than eyes without preoperative mannitolization ( p < 0.05). The ACD, LP, and AL changes by mannitolization were all negatively correlated with corneal endothelial cell loss ( p < 0.05). Conclusion : Preoperative mannitolization can decrease postoperative loss of corneal endothelial cells. The protective effect of preoperative mannitolization on the corneal endothelium may be due to the decreased need for phaco energy and changes in ocular biometry such as ACD, AL, and LP.